COMPARISON BETWEEN THE PROBLEM BASED LEARNING WITH COOPERATIVE LEARNING NUMBERED HEAD TOGETHER (NHT) SEEN FROM MATHEMATICAL POWER OF STUDENTS IN SCIENCE CLASS X OF SMAN 1 LAPPARIAJA - . Sunarti. (Universitas Negeri Makassar, 2016)
This research is a quasi-experimental research, using the nonequivalent pretest-posttest design. The population in this study in a class X IPA at SMAN 1 Lappariaja on the academic year 2015/2016 by number of 188 students. The study involved two experimental class, the class X IPA 4 consisting of 38 student and class X IPA 5 which consists of 36 student selected by cluster random sampling. The first experimental class was treated by applying PBL learning and the second experimental class was treated by applying NHT learning. The instrument used was the echievement test (mathematical power), observation sheets of learning implementation, and student activity sheets. The data obtained were analyzed using descriptive statistics and inferential statistical analysis using analysis of Multivariate Analysis of Varian (MANOVA). The result showed that (1) the mathematical power (the ability of understanding mathematical concepts and communication) after the application of PBL learning is the fair category, while the mathematical problem solving abilities is in the low category, mathematical power improvement in the fair category. Mathematical power (the ability of understanding the concept, communication, and solving math problems) after the application of NHT learning overall is in fair category, the improvement of mathematical is in fair category; (2) there is a difference on students’ mathematical power who are taught through PBL learning and by NHT learning; (3) there is difference on the improvement of understanding the concept between students who were tauhgt throught PBL learning with NHT learning; (4) there is no difference on the communication ability improvement of students who were tauhgt throught PBL learning with NHT learning; (5) there is no difference in problem solving skill improvement of student who were taught through PBL learning and with NHT learning in class X SMA Negeri 1 Lappariaja IPA